Green Biotechnology and Environmental Law: Synergy for Ecological and Social Resilience - Laili Mabrur Rohma; Andry Daniel Dethan; Brayan Multirizky Pradana; Dinda Permata Sari; Cindy Marta Tilana; Vailen Laurens Hiariej; Muhammad Royhan Syahru Ramadhan (Magister Ilmu Lingkungan, Fakultas Teknik dan Sains, UPN Veteran Jawa Timur., 2025)
The accelerating pace of environmental degradation and growing demand for food call for innovative solutions that integrate science and policy. Green biotechnology offers sustainable approaches through genetic engineering of crops, bio fertilizers, bioremediation, and waste management, all of which have proven effective in reducing pollution and enhancing productivity in environmentally friendly ways. However, the application of these technologies in Indonesia faces ethical, social, and legal challenges, including community resistance, regulatory uncertainty, and limited institutional capacity. This study aims to review the interconnection between green biotechnology and environmental law, with analytical scope covering ecological, social, and policy dimensions. A qualitative approach based on literature review and Indonesian case studies was employed to identify potential synergies and major obstacles. The findings indicate that the successful integration of green biotechnology is strongly influenced by regulatory consistency, community participation, and sustained research support. Key recommendations include strengthening environmental governance, enhancing public education to increase technology acceptance, and harmonizing policies in line with sustainable development goals. In conclusion, the synergy between green biotechnology and environmental law forms a crucial foundation for building both ecological resilience and social resilience in the face of global challenges.